ENHANCING INSTRUCTIONAL OUTCOMES THROUGH THE TRANSFORMATIONAL- INSTRUCTIONAL LEADERSHIP MODEL - Agyeman, Nana Yaw Brenya; Aphane, Vanessa (SUKMA: Jurnal Pendidikan, 2025)
School leadership as a discipline continues to recognise the important role of transformational and instructional leadership models (TILM) in enhancing teaching and learning in schools. This leadership model has proven effective in creating a supportive school environment, even in the face of challenges. This study aims to explore how TILM can improve instructional outcomes in schools. Using a qualitative approach and a case study design, the research gathered insights into the experiences and perceptions of participants. Eight individuals were purposively selected from a school, and data was collected through semi-structured interviews. Thematic analysis was employed to identify patterns and themes in the data. The findings indicate that transformational and instructional leaders establish and communicate clear visions and goals to foster collaboration and improvement. However, challenges such as resistance to change and increased workloads can hinder the achievement of these visions and goals. Additionally, while professional development and training empower educators, their effectiveness largely depends on how well they equip teachers to apply theory to practice. These findings highlight the significant role that transformational and instructional leadership plays in enhancing instructional practices within schools. The research suggests that schools should prioritise the implementation of the TILM model to improve teaching and learning outcomes. Ultimately, this study contributes to a deeper understanding of the TILM model's impact on enhancing learning outcomes in educational settings.